2022
DOI: 10.1177/09544062221105987
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Productivity Enhancement of a Solar Still Modified with the Evacuated Tube Heat Pipe using Paraffin Wax

Abstract: The current work involves experimental investigation on a conventional solar still to improve the productivity of fresh water by introducing the evacuated tube thermosyphon heat pipe. The evacuated tube thermosyphon acts as additional heat source to the solar still. The paraffin wax was utilized as latent heat storing medium, filled between the evacuated glass tube and thermosyphon heat pipe to escalate the fresh water productivity during off-sunshine hours. Two identical solar stills, one with three evacuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The customized solar still created 215.7% additional fresh water jointly than the traditional sun. [23] Fresh water production is still good when the evacuated heat pipe is connected directly to the solar panel. revealed that 70% of the total water came from the first step's water generation.…”
Section: Reviews Of Active Ss With Pcm and Without Nano Materialsmentioning
confidence: 99%
“…The customized solar still created 215.7% additional fresh water jointly than the traditional sun. [23] Fresh water production is still good when the evacuated heat pipe is connected directly to the solar panel. revealed that 70% of the total water came from the first step's water generation.…”
Section: Reviews Of Active Ss With Pcm and Without Nano Materialsmentioning
confidence: 99%